2014
DOI: 10.1097/adm.0b013e3182a96466
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Smoking Status and Medical Conditions Among Incarcerated Adults

Abstract: Objectives The rate of smoking among incarcerated adults is over three times that of the general population. Negative health consequences of smoking have prompted many correctional facilities to become tobacco-free. This presents a unique opportunity to examine health conditions associated with motivation to remain tobacco-free following release from prison. We examined this association among individuals who participated in the WISE randomized clinical trial. Methods 247 participants completed a baseline que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Smoking is a harmful and addictive habit which, in addition to being an addiction, gives rise to or exacerbates various pathological conditions [45][46][47][48], including DM and PD. Obradovic and co-workers studied smokers and nonsmokers with T1D or T2D who also had PD and found that smoking had an adverse effect on the periodontal status of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is a harmful and addictive habit which, in addition to being an addiction, gives rise to or exacerbates various pathological conditions [45][46][47][48], including DM and PD. Obradovic and co-workers studied smokers and nonsmokers with T1D or T2D who also had PD and found that smoking had an adverse effect on the periodontal status of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…This may have contributed to reducing the influence of other comorbidities on the association between asthma and hypertension. A strength in the present study is that we considered multiple potential confounders such as obesity 28 , metabolic syndrome 55 , socioeconomic status 56 , psychiatric problems such as stress and depression 37 , and lifestyle variations including smoking and drinking 33 in the association between asthma and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the crude model, age was adjusted for in model 2. In model 3, BMI 28 , smoking (non-smoking, current smoking, ex-smoker) 33 , drinking alcohol (non-drinker, mild to moderate drinker, and heavy drinker) 34 , regular exercise (regular, non-regular, no exercise) 35 , income (quartiles) 36 , perceived stress 37 , and sleep duration 20 were adjusted for. In model 4, serum vitamin D concentration 22 and other allergic diseases (atopic dermatitis, allergic rhinitis) were adjusted for.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking is one of the most important risk factors of disease within detention facilities because, among detainees, the proportion of smokers is 3 times higher than that observed in the general population [28]. This finding highlights the need to implement measures to reduce the consumption of tobacco in a population that presents strong risk factors for chronic respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%